Tradisi Ngalangkang Pambak pada Umat Hindu Kaharingan di Kecamatan Katingan Hilir Kabupaten Katingan (Kajian Agama Budaya dan Psikologi) - Eka, Nali; Megawati, Megawati; Wiranata, Anak Agung Gede; Vienlentia, Raisa (Satya Widya: Jurnal Studi Agama, 2023)
Abstract The death ceremony carried out by Hindu Kaharinngan in Katingan Hilir consists of the stages of the burial ceremony: Tiwah and Ngalangkang Pambak. This ceremony is a mandatory follow-up after the Tiwah, but in reality, Ngalangkang Pambak is no longer held after the ceremony. This ceremony is even carried out as an annual ritual or to commemorate certain events. This research uses a qualitative method with a case study approach. The type of data for this research is primary data sourced from informants and secondary data sourced from supporting data. Data collection methods include observation, interviews, recording, and documentation studies. Data analysis and interpretation procedures in research using a "ground-up" approach. The result of this research, Ngalangkang Pambak is part of a series of Tiwah ceremonies. However, in its development, Ngalangkang Pambka turned into an annual tradition. Ngalangkang Pambak is an event of thanksgiving for the prosperity, good fortune, and health that have been given by the ancestors by cleaning the Pambak or the graves of deceased relatives (ancestors). Ngalangkang Pambak is also means of paying for one's wishes because all requests, whether in the form of work or achievements specifically requested from the ancestors, have all been achieved. The Ngalangkang Pambak ritual creates a feeling of joy and makes life more relaxed and enjoyable, bringing joy to the family that has carried it out because this ritual also means that the family is considered capable of carrying out a form of devotion to their ancestors.